Participatory Governance Dalam Musyawarah Perencanaan Pembangunan Di Kecamatan Sanrobone Kabupaten Takalar - Nurisneni, Nurisneni; Nasrulhaq, Nasrulhaq; Mone, Ansyari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
The purpose of this study was to determine the involvement of participatory governance in the Development Planning Deliberation (Musrembang) in Sanrobone district, Takalar Regency. This study  qualitative research,  that  provided a general picture as a kind of data collected objectively from the field with a type of phenomenology. Data collection techniques  were observation, interviews with a number of informants. Data analysis used qualitative data. The results of this study showed that participatory governance in development planning deliberations in the district of Sanrobone Takalar Regency. Some had been realized optimally in accordance with their objectives, this was seen from the indicator (1) the involvement of direct community participation had been directly involved in musrenbang activities (2) musrenbang activities were still some communities that did not directly involve in development activities due to several constraints / obstacle (3) the community was very auntusian in attending Musrenbang activities (4) many people gave ideas or advices for the smoothness of musrenbang (5) people hoped to be responsible and participate in the implementation of musrenbang activities.Keywords: Participation Involvement, Participation Rate